Semantics of metalinguistic focus - Li, Haoze (Proceedings of the Amsterdam Colloquium, 2025)
Focus on metalinguistic aspects of utterances, despite being a robust phenomenon in nat ural language, is unamenable to the standard semantics of focus. Nonetheless, I show that this type of focus can be understood in terms of standard focus semantics, if we incorporate insights from Pott’s [21] multi-dimensional semantics of mixed quotations. Moreover, I de velop a scope-taking account to compositionally synthesize focus semantics and quotation semantics.